Arteria Renalis Accessoria - Siti Aminah Tri Susilo Estri (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2001)
The vascularisation of the kidneys varies in number and location. The kidney that has two or more renal arteries found in 25-30% of population. The variation of renal arteries arises as result of the persistence of embryonic vessel that normally degeneratic when definitive renal arteries are formed.Vascularisation variation of the kidney in the forms of renalis artery and accessory renal artery were found in one of five cadavers dissected in the Laboratory of Anatomy, Faculty of Medicine, Muhammadiyah University of Yogyakarta.The left kidney has one principal artery and one accessory artery that branched from abdominal aorta. The accessory renal artery was located in the inferior of the principal artery and passed the inferior polus of the left kidney. In this case no obstruction of the ureter nor hydronephrosis was found as the main clinical feature usually observed in the cases.Vaskularisasi pada ren bervariasi pada jumlah dan posisi . Pada 25% - 30% populasi ditemukan adanya ren yang mempunyai 2 atau lebih arteria renalis. Variasi ini berasal dari tetap adanya vasa darah embryonal yang seharusnya mengalami degenerasi ketika vasa renalis (definitive) terbentuk.Variasi vaskularisasi pada ren berupa arteria renalis dan satu arteria renalis accessoria telah ditemukan pada saat diseksi kadafer ke-5 kali di Laboratorium Anatomi Universitas Muhammadiyah Yogyakarta.Ren sinistra tampak mempunyai a. renalis sinistra (principalis) dan satu a. renalis accessoria, yang dipercabangkan langsung dari aortae abdominalis. Arteria renalis accessoria terletak di sebelah inferior dari a. renalis sinistra dan pergi ke polus inferior ren sinistrae. Pada kasus ini tidak ditemukan adanya obstruksi ureter maupun hidronefrosis.